A national survey of music education majors' confidence in teaching improvisation. (November 2016) - Bernhard, H. Christian; Stringham, David A.
The purpose of the study was to investigate undergraduate music education majors' confidence in teaching improvisation, according to the NAfME (1994) K–12 Achievement Standards. Specific research questions were: 1) How confident are music education majors in implementing the 11 improvisation achievement standards for grades K–12? 2) How confident are they in their own improvisation ability? 3) How interested or motivated are they in learning more about how to teach improvisation? 4) Are there differences in confidence among music education majors by year in school? 5) Are there differences in confidence among music education majors by primary instrument? Participants were 397 undergraduate music education majors from National Association of Schools of Music (NASM) accredited institutions in the United States, whose confidence in teaching improvisation decreased as grade level increased. Sophomore and senior means were higher than freshman and junior means, and slight differences were observed by primary instrument (woodwind, piano, brass, voice, string, percussion, in increasing confidence). Participants reported slight to moderate confidence in their own ability to improvise, but moderate to great interest in learning more about how to teach improvisation.